Sex differences in epigenetic age in Mediterranean high longevity regions - Engelbrecht, Hannah-Ruth; Merrill, Sarah M.; Gladish, Nicole; MacIsaac, Julie L.; Lin, David T. S.; Ecker, Simone; Chrysohoou, Christina A.; Pes, Giovanni M.; Kobor, Michael S.; Rehkopf, David H. (Frontiers in Aging, 2022)
Sex differences in aging manifest in disparities in disease prevalence, physical health, and lifespan, where women tend to have greater longevity relative to men. However, in the Mediterranean Blue Zones of Sardinia (Italy) and Ikaria (Greece) are regions of centenarian abundance, male-female centenarian ratios are approximately one, diverging from the typical trend and making these useful regions in which to study sex differences of the oldest old. Additionally, these regions can be investigated as examples of healthy aging relative to other populations. DNA methylation (DNAm)-based predictors have been developed to assess various health biomarkers, including biological age, Pace of Aging, serum interleukin-6 (IL-6), and telomere length. Epigenetic clocks are biological age predictors whose deviation from chronological age has been indicative of relative health differences between individuals, making these useful tools for interrogating these differences in aging. We assessed sex differences between the Horvath, Hannum, GrimAge, PhenoAge, Skin and Blood, and Pace of Aging predictors from individuals in two Mediterranean Blue Zones and found that men displayed positive epigenetic age acceleration (EAA) compared to women according to all clocks, with significantly greater rates according to GrimAge ( = 3.55; P =1.22 x10-12), Horvath ( = 1.07; P = 0.00378) and the Pace of Aging ( = 0.0344; P = 1.77 x10-08). Other DNAm-based biomarkers findings indicated that men had lower DNAm-predicted serum IL-6 scores ( = -0.00301, P = 2.84 x10-12), while women displayed higher DNAm-predicted proportions of regulatory T cells than men from the Blue Zone (P = 0.0150, 95% Confidence Interval [0.00131, 0.0117], Cohen’s d = 0.517). All clocks showed better correlations with chronological age in women from the Blue Zones than men, but all clocks showed large mean absolute errors (MAE >30 years) in both sexes, except for PhenoAge (MAE < 5 years). Thus, despite their equal survival to older ages in these Mediterranean Blue Zones, men in these regions remain biologically older by most measured DNAm-derived metrics than women, with the exception of the IL-6 score and proportion of regulatory T cells.